2019
DOI: 10.25301/jpda.281.41
|View full text |Cite
|
Sign up to set email alerts
|

Outcome-based Dental Education and Identification of Practice Gaps; A Narrative Review

Abstract: Undergraduate dental education aims to provide the society with competent dental graduates that are able to serve in the community as independent practitioners. The rotational clinical training provided in our current dental settings do not fully prepare dental graduate for comprehensive dental care as the focus is more on subject areas rather than as a whole. Outcome-based dental education defines certain outcome-competencies that are essential part of dental curriculum and also provide a roadmap for curricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…It is not limited to executing a few dental procedures; rather, it includes knowledge, experience, critical thinking, problem-solving skills, professionalism, technical and procedural skills [ 7 ]. All the components mentioned above are required in combination to provide holistic patient care [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is not limited to executing a few dental procedures; rather, it includes knowledge, experience, critical thinking, problem-solving skills, professionalism, technical and procedural skills [ 7 ]. All the components mentioned above are required in combination to provide holistic patient care [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, CBE pattern of assessment came in agreement with the recommendations of Deogade & Naitam, 2016 about the outcome‐based assessment methods, and as found by Khanna and Mehrotra (2019) the CBE exposed the students to variable clinical challenges that improved their critical thinking and decision making. Khanna and Mehrotra (2019) and Ghafoor (2019) further confirmed that the CBE help the students to evolve from the discipline‐based and teacher‐centered TE, to a student‐centered, outcome‐based process that would gain their interest. In addition, Ben‐Gal et al.…”
Section: Discussionmentioning
confidence: 84%
“…Competency‐based education dictates a shift from the TE which is teacher‐centered, examination‐driven, time‐based, and discipline‐based (Khanna & Mehrotra, 2019; Taleghani et al., 2004; Yip & Smales, 2000), to a student‐centered education that enriches the students' skills in critical thinking, problem‐solving, and autonomous self‐assessment, which further help them perform better comprehensive patient care and develop ethical values and professionalism for better community‐based services (Behbehani, 2003; Deogade & Naitam, 2016; Field, Cowpe, & Walmsley, 2017; Ghafoor, 2019; Hendricson & Cohen, 1999; Hsu et al., 2015; Khanna & Mehrotra, 2019; Puryer, Woods, Terry, Sandy, & Ireland, 2018; Roudsari, 2018; Whitney, Walton, Aleksejuniene, & Schönwetter, 2015; Yip & Smales, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A review of scholarly works supporting outcomes and OBE curriculum development as a transformational school reform process has been widely published over the last five years (Yen, Sekar & Ansari, 2016;Alkatheri et al, 2017;Bateman et al, 2017;D'cruz, 2017 Edaño, Umayan, 2017;Kasturi, 2017;Vivek, 2017;Nakkeeran et al, 2018;Liebelt et al, 2018;Ayyappan et al, 2019;Ghafoor & Khan, 2019;Gunarathne et al, 2019;Jeppesen et al, 2019;Khanna & Mehrotra, 2019;Iqbal, 2020;Li, 2020;Prihantoro, 2020;Rao, 2020). The variations in the processes in the selected studies are suggestive of different sources considered in formulating the outcomes.…”
Section: Introductionmentioning
confidence: 99%